ChemInform Abstract: Novel Chemical Synthesis and Characterization of CeTi2O6 Brannerite. Issue 36 (9th September 2014) - Kong, Linggen; Gregg, Daniel J.; Karatchevtseva, Inna; Zhang, Zhaoming; Blackford, Mark G.; Middleburgh, Simon C.; Lumpkin, Gregory R.; Triani, Gerry
Abstract The title compound is synthesized in aqueous medium from a mixture of titanium(IV) bis(ammonium lactato)dihydroxide and Ce(NO3)3 (sintering between 800 and 1400 °C).